Chronic Racemic and (S)-Methadone Treatment Reduces hERG Gene Expression in Human Primary Cardiomyocytes - Mokhtar, Noor Fatmawati; Hussin, Mohd Farid (Cardiology and Cardiovascular Medicine, 2017)
Background: Methadone is now increasingly being used to control opioid withdrawal symptoms, and recently, chronic pain. With increasing reports of cardiac problems induced by methadone, we aimed to determine effect of methadone on hERG expression after chronic treatment with racemic and the two enantiomers (S- and R-) of methadone. The molecular mechanism underlying methadone-disrupted hERG expression in human primary cardiomyocytes was also investigated. Methods: Cardiomyocytes were treated for 5 days with racemic-, (S)- and (R)-methadone at 3, 2, and 7 μM, respectively. The effect of racemic-, (S)-, and (R)-methadone on hERG, SGK3, and Hsp90 mRNA expression was examined by real-time PCR. Protein expression of hERG was determined by western blotting. Results: Chronic treatment with racemic- and (S)-methadone but not (R)-methadone, significantly suppressed hERG mRNA expression and down-regulated SGK3 mRNA expression. However, hERG protein expression was only affected by chronic (S)-methadone treatment. Hsp90 mRNA expression was not affected by any form of methadone. Conclusions: We conclude that after chronic treatment, racemic- and (S)-methadone have similar potencies in reducing hERG mRNA expression, and this act via disruption of SGK3 expression.